A Romantic Vision of Millenarian Disease: Placing and Displacing Death in Mary Shelley's The Last Man - Antonio Ballesteros González (Miscelánea: A Journal of English and American Studies, 1996)
This article deals with Mary Wollstonecraft Shelley’s The Last Man (1826), a dystopian and pessimistic narrative which focuses on the representation of death from a millenarian and apocalyptic perspective. Death is symbolized in the novel by a mysterious plague which both factually and metaphorically menaces mankind with (almost) complete extermination. The study centres itself upon the literary and ideological consequences of the plague in the anachronistically Romantic context depicted by Shelley and on the connections with our fin de siècle and millenarian situation at the turn of a new century.